Peningkatan Ekonomi Lokal melalui Diversifikasi Olahan Produk Sampingan (By-Product) Pisang di KWT Mekarsari Desa Jatisaba Kabupaten Banyumas: Enhancing Local Economy through Banana By-Product Diversification at Mekarsari Women Farmer Group, Banyumas Regency - Alpha Nadeira Mandamdari; Altri Mulyani; Anggi Fitria Cahyaningsih; Pepita Haryanti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Banana plants in Jatisaba Village, Banyumas Regency, offer abundant raw material potential; however, their utilization remains limited to the fruit, while by-products such as banana blossom and leaves have not been economically optimized. This community service program aims to empower the Mekarsari Women Farmer Group (KWT) by diversifying its zero-waste food products to enhance family income. The implementation method employed a participatory approach, encompassing socialization, technology transfer training for processing, and production management assistance. Technological intervention focused on processing banana hearts and young leaves into marketable chips, supported by the facilitation of an oil spinner machine. The results indicated a significant improvement in partner competence, evidenced by an increase in the participants' average knowledge scores. The average score increased from 44.6 (Poor) in the pre-test to 86.6 (Very Good) in the post-test. With this assistance, KWT Mekarsari successfully produced marketable product samples, marking their readiness to proceed to the home-scale commercialization stage.